Place identity through plant motif on streetscapes in the Royal Town of Kuala Kangsar, Perak, Malaysia - Mohd Khalid, Intan Khasumarlina (2020)
The Malay Royal Towns in Malaysia are the finest examples of the evolution of the early Malay settlements of the 16th century. However, the identity and characteristics of Malay Royal towns are still ambiguous and constantly threatened by inordinate changes due to rapid industrialisation, economic development and urbanization. The extensive urbanization and rapid development in most historic towns have significantly eroded the identity, sense of place and physical attributes of the Malay Royal Towns. In addition to existing historical monuments, which are the pride of the Malay royal town, the peculiarity of their natural heritage factors that indicate the identity of the place are very much required in terms of preservation and enhancement. The scope of this research covers all of the properties which identifies cultural significance mainly representing ornaments through plants motif on the streetscape of royal towns. This study aims to suggest the plant motif most used in ornaments on streetscapes for determining the identity of the Royal Town of Kuala Kangsar, Perak. The main strategy of this research is to employ a case study. The study is designed in four stages which consist of an initial background review of the royal town, its historical development as well as issues and problems identifiable to develop the research questions. A conceptual framework and research methodology shall be developed in the second stage. In the third stage, a research will be conducted in the Royal Town of Kuala Kangsar, Perak. The study shall adopt the qualitative methodological approach in data collection and analysis, whereby data collected are obtained from semi-structured interviews with experts, content analysis and supported with a public survey in Kuala Kangsar. The final results will then be derived from a convergence of the data in an analytical triangulation process. The findings of this study is aimed to provide insights into designing the royal town while taking into account the type of plant criteria which constitutes Kuala Kangsar. Additionally, the finding will also list suitable criteria of plant motif appropriate for the Royal Town Kuala Kangsar, Perak. Hence, special attention should be provided in suggestive plant motif for streetscapes in order to reinforce the place identity of the Royal Town Kuala Kangsar, Perak. The result will hopefully assist the city council to focus on the plants' character or appearance as motif for streetscape ornaments and furniture to further enhance the identity of the Royal Town Kuala Kangsar, Perak. Finding of this research informs that plant motif is one of the factors that should be highly considered in securing local place identity for streetscapes design of the royal town in Malaysia.